1995
DOI: 10.1016/0925-4439(95)00071-b
|View full text |Cite
|
Sign up to set email alerts
|

Induction of hepatic CYP1A2 by the oral administration of caffeine to rats: lack of association with the Ah locus

Abstract: Caffeine was administered to male Wistar albino rats for two weeks at three concentrations, namely 0.1, 0.2 and 0.3%, and hepatic cytochrome P450-dependent mixed-function oxidase determined. Caffeine administration gave rise to a marked, dose-dependent increase in the O-deethylation of ethoxyresorufin and, to a lesser extent, in the O-depentylation of pentoxyresorufin. Erythromycin N-demethylase, p-nitrophenol hydroxylase and lauric acid hydroxylase activities, as well as total cytochrome P450 content were una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 38 publications
2
23
0
2
Order By: Relevance
“…No such effect was observed when decaffeinated tea was employed, but was restored when decaffeinated tea was supplemented with the normal amount of caffeine, indicating that the xanthine is largely responsible for this effect, and may be associated with the documented upregulation of the cytochrome P450 enzyme CYP1A2 by caffeine, so modulating the metabolic pathways of the carcinogen (Ayalogu et al 1995;Bu-Abbas et al 1999a;Chen et al 1996). Subsequently, metabolic studies revealed that treatment of rats with green tea for 6 weeks led to an increase in the excretion of the N-glucuronide of Nhydroxy-IQ, a detoxication product, and, moreover, the same treatment stimulated the excretion of IQ in the form of the inactive 5-hydroxy-IQ, present in the urine in the form of conjugates, indicating an overall shift of the metabolism towards the detoxication (Embola et al 2001a(Embola et al , 2001b.…”
Section: Introductionmentioning
confidence: 91%
“…No such effect was observed when decaffeinated tea was employed, but was restored when decaffeinated tea was supplemented with the normal amount of caffeine, indicating that the xanthine is largely responsible for this effect, and may be associated with the documented upregulation of the cytochrome P450 enzyme CYP1A2 by caffeine, so modulating the metabolic pathways of the carcinogen (Ayalogu et al 1995;Bu-Abbas et al 1999a;Chen et al 1996). Subsequently, metabolic studies revealed that treatment of rats with green tea for 6 weeks led to an increase in the excretion of the N-glucuronide of Nhydroxy-IQ, a detoxication product, and, moreover, the same treatment stimulated the excretion of IQ in the form of the inactive 5-hydroxy-IQ, present in the urine in the form of conjugates, indicating an overall shift of the metabolism towards the detoxication (Embola et al 2001a(Embola et al , 2001b.…”
Section: Introductionmentioning
confidence: 91%
“…Erucin and sulforaphane, both small molecular weight aliphatic compounds, are clearly strong inducers of CYP1 family expression despite the fact that structurally they are unlikely to be Ah receptor agonists. However, it should be borne in mind that up-regulation of the CYP1 family, independent of binding to the Ah receptor, has been reported (Ayalogu et al, 1995;Boyd et al, 1995;Lesca et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However, the modulation effect observed in preclinical studies could be attributed to caffeine present in green tea because caffeine has been shown to be a potent inducer of CYP1A2 (21,22). This may explain the lack of clinical effect on human CYP1A2 activity observed in our study because Polyphenon E is a decaffeinated green tea catechin product.…”
Section: Discussionmentioning
confidence: 59%